Molecular Typing of Staphylococcus aureus Isolated from Patients with Autosomal Dominant Hyper IgE Syndrome - Sastalla, Inka (Pathogens, 2017)
Autosomal dominant hyper IgE syndrome (AD-HIES) is a primary immunodeficiency caused by a loss-of-function mutation in the Signal Transducer and Activator of Transcription 3 (STAT3). This immune disorder is clinically characterized by increased susceptibility to cutaneous and sinopulmonary infections, in particular with Candida and Staphylococcus aureus. It has recently been recognized that the skin microbiome of patients with AD-HIES is altered with an overrepresentation of certain Gram-negative bacteria and Gram-positive staphylococci. However, these alterations have not been characterized at the species- and strain-level. Since S. aureus infections are influenced by strain-specific expression of virulence factors, information on colonizing strain characteristics may provide insights into host-pathogen interactions and help guide management strategies for treatment and prophylaxis. The aim of this study was to determine whether the immunodeficiency of AD-HIES selects for unique strains of colonizing S. aureus. Using multi-locus sequence typing (MLST), protein A (spa) typing, and PCR-based detection of toxin genes, we performed a detailed analysis of the S. aureus isolates (n = 13) found on the skin of twenty-one patients with AD-HIES. We found a low diversity of sequence types, and an abundance of strains that expressed methicillin resistance, Panton-Valentine leukocidin (PVL), and staphylococcal enterotoxins K and Q (SEK, SEQ). Our results indicate that patients with AD-HIES may often carry antibiotic-resistant strains that harbor key virulence factors.